UV induced changes in bismuth oxychloride–filled polycarbonate composite films - Vijayashri Ashok Kandagal; Blaise Lobo (Academia Materials Science)
Bismuth oxychloride (BiOCl)–filled polycarbonate (PC) composite films have been prepared at five different filler levels (FLs), that is, at 0, 5, 15, 25, and 35 wt.% (of BiOCl in PC), by using the solution casting method. These composites were irradiated with UV-C radiation at a wavelength of 254 nm for four hours and were studied before and after UV-C irradiation. The prepared composites showed three fluorescence emission peaks for pristine PC, at wavelengths of 415, 440, and 467 nm, and the emission peak intensity increases with an increase in FLs and exposure time to UV irradiation. There is a structural transformation of the sample, from the amorphous nature of PC to the crystalline nature of BiOCl-filled PC composite samples, which has been confirmed by the XRD technique; the degree of crystallinity has increased with an increase in FL. SEM images confirm that surface morphological changes take place due to an increase in BiOCl content in the PC matrix with an increase in FL. The uniform distribution of BiOCl in PC has been confirmed by observing the AFM images. A single-step decomposition phenomenon is observed from the TGA curves, and pristine PC has greater mass loss and thermal stability among all the filled and irradiated BiOCl-filled PC composite films.